GE_GERICHTE P/11219/2010 vom 28. November 2014 - GE Cour de justice (2014)
CONTRAINTE SEXUELLE; FRAIS DE LA PROCÉDURE; INDEMNITÉ(EN GÉNÉRAL) | CEDH.6.2; Cst.32.1; CPP.10.3; CPP.135.2; CPP.136.2.B; CPP.421.1; CP.189.1; RAJ.16.1